Financial Feasibility Analysis of Pickled Skipjack Tuna Products at Titiefood MSMEs in Gorontalo City - Andi Desiah Pradilia; Reinal Putalan; Triatmi Agustina Landjoi; Mawar Hasyim (Hasanuddin University, 2025)
This study aims to analyze the financial feasibility of the pickled skipjack tuna production business at the Titie Food MSME in Gorontalo City through the R/C Ratio, Break Even Point (BEP), and Payback Period (PP) approaches. The research method uses a quantitative descriptive approach by collecting data on fixed costs, variable costs, production volume, revenue, and initial investment incurred by the MSME. The results show that the total fixed costs of the Titie Food MSME are IDR 8,606,165.46 per month, with total variable costs reaching IDR 37,275,000.00 for a production capacity of 2,100 units. The R/C Ratio analysis shows a value greater than 1, which indicates that the business is in a profitable condition and is feasible to run. The BEP analysis shows that the business reaches the break-even point at sales of 703 units or IDR 21,090,000, while actual production far exceeds this value, thus providing a high safety margin. Furthermore, the Payback Period (PP) analysis shows that the initial investment of IDR 413,178,997.00 can be recovered within 24.13 months, or approximately two years. Overall, the results of this study confirm that the pickled skipjack tuna production business at the Titie Food MSME is financially viable and has good long-term development prospects